An Excel/VBA Teaching-Learning Solution of Velocity Triangle Analysis of Hydraulic Turbines - Karn, Ashish; Mahawar, Rohit; Dwivedi, Priyanshu; Agarwal, Raghav (Journal of Engineering Education Transformations, 2023)
Abstract :This study reports an investigation into the use of computational techniques applied to selected Turbo machinery problems. Students in their third year of a B.S./ B.Tech in Mechanical Engineering program often focus on this topic. As a result of being exposed to an overwhelming quantity of hypothetical ideas, loads of recipes, and references from information handbooks, students sometimes become overwhelmed during lessons on Turbomachinery. An intuitive learning scenario, such as a computerized setting, can be useful in some circumstances. Thus, computer-based exercises are essential to improve dynamic learning. This study will present an alternate technique of demonstrating the turbo machinery analysis using Excel/VBA. The classroom isn't the only setting where a powerful computer application can alter the way subjects are learned and homework is completed. Both students and teachers can benefit from the introduction of this technology. Students will benefit from having this tool available because it will eliminate the need for lengthy calculations and allow them to easily observe the effects of changing values on various variables, thereby improving their understanding of the subject matter and increasingtheir interest in and enthusiasm for studying it. Further, it will aid educators in conveying a variety of turbomachinery ideas to their students. In addition, students can use these resources in the project's design phase. This program can do more than just solve the equations; it can also tell you how the various parameters influence the forces. This means that students can complete as many calculations as they need with the touch of a button, without the risk of making a mistake or growing bored with the process. Keywords : Computational tool; engineering tool; Excel/VBA; innovative pedagogy; turbomachinery tool.